2019
DOI: 10.3390/microorganisms7100463
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Prevents Sensitization to Oral Antigen and Subsequent Increases in Intestinal Tight Junction Permeability in Juvenile–Young Adult Rats

Abstract: Increased intestinal permeability is thought to underlie the pathogenesis of food allergy. We explore the mechanism responsible for changes in the morphology and function of the intestinal barrier using a rat model of food allergy, focusing on the contribution of intestinal microbiota. Juvenile–young adult rats were sensitized with ovalbumin and treated with antibiotics or probiotics (Clostridium butyricum and Lactobacillus reuteri), respectively. The serum ovalbumin-IgE levels, intestinal permeability, histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…In animal models of FA, oral sensitization to ovalbumin (OVA) induced an increase in the lactulose/mannitol (La/Ma) ratio (indicative of increased intestinal permeability) in excreted urine after two weeks of allergen intake, followed by an increase in serum anti-OVA IgE and a downregulation of ZO-1, claudin-2, claudin-8, and claudin-15 gene expression but upregulation of claudin-9 [ 106 ]. Similarly, rats with FA to OVA demonstrated downregulation of ZO-1, occludin, and claudins 1, 3, 5, 7, 8, 9, and 15 in intestinal tissue; which was accompanied by a widening and shortening of tight and adherent junctions, an increase in excreted La/Ma ratio, and a relocation of some TJ proteins in enterocytes [ 108 ]. The increase in intestinal permeability has been linked to intestinal mastocytosis and IL-9 overexpression ( Figure 4 ), which are associated with a predisposition to clinical manifestations, such as diarrhea, in the absence of allergen sensitization [ 104 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…In animal models of FA, oral sensitization to ovalbumin (OVA) induced an increase in the lactulose/mannitol (La/Ma) ratio (indicative of increased intestinal permeability) in excreted urine after two weeks of allergen intake, followed by an increase in serum anti-OVA IgE and a downregulation of ZO-1, claudin-2, claudin-8, and claudin-15 gene expression but upregulation of claudin-9 [ 106 ]. Similarly, rats with FA to OVA demonstrated downregulation of ZO-1, occludin, and claudins 1, 3, 5, 7, 8, 9, and 15 in intestinal tissue; which was accompanied by a widening and shortening of tight and adherent junctions, an increase in excreted La/Ma ratio, and a relocation of some TJ proteins in enterocytes [ 108 ]. The increase in intestinal permeability has been linked to intestinal mastocytosis and IL-9 overexpression ( Figure 4 ), which are associated with a predisposition to clinical manifestations, such as diarrhea, in the absence of allergen sensitization [ 104 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…Increased permeability is thought to be associated with intestinal pathogenesis ( 17 , 18 ). The intestinal mucus in juvenile animals is immature, which is easy to be infected by intestinal bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have examined the effect of anti-allergic probiotics on intestinal barrier function. Among them, a mixture of Lactobacillus strains that reduces allergen sensitization in Bet v1 pollen-sensitized mice upregulates the expression of occludin and the TJ molecule ZO-1, increases total intestinal and serum IgA levels, and improves the function of the gut epithelial barrier [48]; Clostridium butyricum and Lactobacillus reuteri treatments which downregulate allergic immune response in a rat model of food sensitization decrease intestinal permeability and increase tight junction expression [49]. Additionally, it has been demonstrated that probiotic lactobacilli ( L. rhamnosus 19070-2 and L. reuteri DSM 12246) reduce small intestinal permeability in children with atopic dermatitis [50].…”
Section: Discussionmentioning
confidence: 99%